Análisis de factibilidad del uso de sensores para la gestión de clientes en el Gimnasio Warrior Fitness Club. - Torres Banchón, Darwing Joel (2024)
This case study has been carried out with the purpose of verifying if the installation of new technologies such as sensors, among them are motion sensors, air humidity sensors, pressure sensors and water flow sensors among others. After a long and exhaustive research it has been concluded that actually implementing this type of technology is both feasible in terms of benefits, functionality and cost-benefit, the latter being the one most appreciated by gym owners or companies interested in acquiring this type of technology to improve the effectiveness, safety, efficiency and above all the loyalty of their customers. The research of this document covers fields such as health, customer loyalty, improvement of habits, surveys, difference between one or another equipment of the same segment, etc. To be able to choose according to the needs of the reader's interest.